Sistem Peradilan Pidana Dan Jaminan Hak Asasi Manusia (HAM) Terhadap Tersangka Tindak Pidana - Evin Dwi Nugroho; Pujiyono Pujiyono (JURNAL BELO, 2022)
The purpose of this research is to find out more about the criminal justice system regarding human rights and what rights must be obtained by suspects of criminal acts. The method used in this research process is a normative juridical research method by examining legal facts and paying attention to the rules, values, principles, and norms regulated in the legislation. The approach used in this research is an approach to legislation, analysis, and concepts. The results of this study are the efforts to reform Indonesian criminal law and efforts to overcome them, the implementation of criminal law enforcement policies for the prevention of criminal acts based on laws and regulations that are not in line with current developments. The criminal justice system is in an effort to enforce the rights and guarantees of suspects in the legal procedural law of the criminal justice system. Looking at the current condition of the criminal justice system, it is often found that the rights of suspects are ignored.